Cross-cultural, values and ethics differences and similarities between the US and Asian countries. Issue 3 (30th September 2014) - Garcia, Fredi; Mendez, Diana; Ellis, Chris; Gautney, Casey
Abstract : Purpose: – This article aims to investigate the differences and similarities among cross-cultural, values and ethics between the USA and Asian countries. This article analyzes the degree of cultural distance between USA and Asian countries and the impact it has in companies. It examines the comparison between the USA and China's value system. It also assesses how idealism and relativism impact individual ethical decision-making. In addition, this article examines the impact that globalization, foreign direct investment (FDI) and trade have in the Chinese culture and other countries. Design/methodology/approach: – The data for this research paper were collected from the following models: Ethics Position Questionnaire of Forsyth, Rokeach Values Survey, Hofstede model, GLOBE model and Wilcoxon test. The main sources used for this research were the Journal of Technology Management in China and the EBSCO database. Findings: – The research found that Western cultures tend to be more individualistic, while Asian countries tend to be very collective. This study also found that the type of value system that each culture holds depends on the type of government. This research also found that researchers have discovered that American managers are more loyal to their ethical beliefs, rather than to their superior's or company's ethical beliefs. While eastern Asian cultures focus more on the importance of acting in the best interests of the company's superior. The study also found that it is extremely important for foreigners to build a relationship with Chinese business professionals before they do business negotiations. In addition, the study found that globalization, FDI and trade do make a significant cultural difference in some cultural dimensions. Originality/value: – It contributes to the literature by analyzing the different measurements in value, ethics and cultural differentiation. This research wants to demonstrate the importance of cultural differences, ethics and values across different countries and cultures. It also provides factual evidence that it's important to understand these differences to be a successful global manager. In addition, it contributes to this literature by analyzing the effect that globalization, FDI and trade have in national cultures.